Respostas
respondido por:
5
a +b = 12 ⇒⇒⇒⇒⇒⇒⇒ a= 12 -b
a- b = 10 a= 12 -1
12 -b -b = 10 a= 11
-b -b= 10 -12
-2b = -2 . (-1)
2b = 2
b = 2/2
b= 1
a² - b²
11² - 1²
121 - 1
120
Bons estudos!
a- b = 10 a= 12 -1
12 -b -b = 10 a= 11
-b -b= 10 -12
-2b = -2 . (-1)
2b = 2
b = 2/2
b= 1
a² - b²
11² - 1²
121 - 1
120
Bons estudos!
Anônimo:
tabata, me ajuda na minha questão??? http://brainly.com.br/tarefa/2317728
respondido por:
4
se
a+b=12
a-b=10
logo
a²-b²=
(a+b)(a-b)=
12×10=120
a+b=12
a-b=10
logo
a²-b²=
(a+b)(a-b)=
12×10=120
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás